Pre-service teachers’ perceptions towards the implementation of multimodal texts in microteaching classes - Haryyadi, Jullius Christ Addel; Rohmah, Zuliati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
In the digital age, technological advances impact EFL language instruction in Indonesia. After examining the current and future demands of education, prospective educators need to attain the minimum standards to fulfill students' needs in the twenty-first century. Multimodal texts in education are one way to solve today's pedagogical needs. The current study explores pre-service teachers' perceptions of their performance in utilizing multimodal texts in microteaching classes. Data were collected from the 6th-semester students from the English Language Education Study Program, the Faculty of Cultural Studies, Universitas Brawijaya, Indonesia. This research applied mixed methods, combining data collection from observation, questionnaires as primary sources, and a focus group discussion (FGD) to support the data. Then, the questionnaire data were analyzed quantitatively, and data from the FGD were coded and analyzed using thematic analysis. The finding shows that the pre-service teachers applied five types of multimodal texts in microteaching classes. In addition, although most of them perceive positively toward the use of multimodal texts in their teaching practice, there are still challenges in implementing digital-based multimodal texts, such as limited access to digital applications and confusion in integrating digital applications into learning activities.